Spatial Distribution, Temporal Variation and Specificity of Microhabitat of Tropisternus Species (Coleoptera: Hydrophilidae) in Permanent Ponds - Gomez Lutz, Maria Constanza (2015)
The spatial distribution and temporal variation of 11 species of Tropisternus were analyzed in two permanent ponds located in the province of Corrientes, Argentina. Samples were collected every 15 days, between October 2010 and March 2011. The species recorded were Tropisternus collaris (Fabricius), Tropisternus ovalis Castelnau, Tropisternus laevis (Sturm), Tropisternus lateralis limbatus (Brullé), Tropisternus longispina Fernández & Bachmann, Tropisternus carinispina Orchymont, Tropisternus bourmeisteri Fernández & Bachmann, Tropisternus apicipalpis (Chevrolat), Tropisternus dilatatus Bruch, Tropisternus obesus Bruch, and Tropisternus ignoratus Knisch. The first four were present in higher proportions than the remaining during most of the study period. The spatial distribution of individuals was mostly related to the homogeneity or heterogeneity of the ecosystem in relation to microhabitats with aquatic vegetation: In ponds with different microhabitats, individuals were mainly aggregated, whereas in ponds with homogenous features, individuals were randomly distributed. However, when species were analyzed individually, the spatial distribution and the use of microhabitat by each species were different with respect to preference and behavior.